Finite element based modelling and analysis of dragline boom structure - Shukla A.; Rai P. (My University, 2025)
Dragline is the most widely used machine in opencast mining. It is used for removal of overburden in coal mining. During the digging process machine experiences various loadings on its front end structure, which typically consist of boom, bucket and wire ropes. These loads tend to develop stresses in each cycle of the dragline and causing the structural damage.The bucket is connected to the boom by hoist ropes on the top of the boom using boom point sheaves. As bucket start to dig, the forces on the boom start to increase and reached their maximum value at the end of digging cycle. In the current work, only the dragline boom is considered for investigation of stresses. Due to the complexity of the structure, only overall structural behaviour is predicted, and also a single joint is separately analysed for better understating of stresses acting near the joint. ANSYS 18.0 software is used for analysis purpose, and Solidworks software is used for three-dimensional model creation. Beam-to-solid sub-modelling is implemented inside the ANSYS software to minimize the computation time and requirements. © 2020, Books and Journals Private Ltd. All rights reserved.